Pengaruh Pengalaman Kerja dan Motivasi terhadap Kinerja Pegawai Pemerintahan Kota Medan - Parmin Hasibuan (Fakultas Ekonomi Dan Bisnis Universitas Tjut Nyak Dhien, 2023)
This research was carried out at the Medan City Government with a population and sample of 55 employees. This research instrument is a questionnaire with a Likert scale model. Requirements tests are carried out to test normality. The data analysis technique used is the Multiple Regression technique at a significance level of a = 0.05. The results of this research show that Work Experience (X1) has a significant and influential effect on the performance of Medan City Government Employees. The calculated t is greater than the t table (2.954 ˃ 1.674) with a significant value of 0.03. Meanwhile, Motivation (X2) has a significant influence on the performance of Medan City Government Employees with a calculated t value greater than the t table (4.180 ˃ 1.674) with a significant value of 0.000. Based on the SPSS output, it is known that the R squared value is 0.350, meaning that the variance in the Performance variable can be explained by the Work Experience and Motivation variables by 35 percent, while the remaining 70 percent is explained by other variables not included in this model. In other words, there are still other independent variables that influence performance.